Canine Parvovirus Infection: Clinical, Haemato-Biochemicaland Oxidative Stress Profiles - Mishra, Ankita; Singh, Brejesh; Gupta, Devendra Kumar; Jain, Sachin; Gattani, Anil (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study covered 57 dogs presented with haemorrhagic gastroenteritis at Veterinary Clinical Complex, Jabalpur from May to October 2024 which were confirmed positive for canine parvovirus via PCR. The most frequently observed clinical manifestations in this study were inappetence, frothy vomition, bloody diarrhoea, dehydration and depression. The haematological alterations revealed decreased levels of haemoglobin, total erythrocyte count, total leukocyte count, packed cell volume, neutrophilia and lymphopenia in CPV affected dogs as compared to healthy dogs. The serum levels of alkaline phosphatase and alanine aminotransferase were elevated, while the total protein and albumin levels were decreased. Oxidative stress parameters, viz., malondialdehyde was significantly higher, while reduced glutathione and catalase values were significantly lower in CPV affected dogs as compared to healthy controls.